Guinness world records 2011. Gamer's edition. - Guinness World Records Limited ([London] : Guinness World Records, 2011)
Lists records, superlatives, and unusual facts about computer and video games, and includes interviews with champion gamers, tips on play, and profiles of the best-selling games.
Includes index.
Keywords: Video games -- Miscellanea; Video games -- History; Curiosities and wonders; World records; Video games; Curiosities and wonders; Video games; World records; Video games -- Miscellanea; Computer games -- Miscellanea; Curiosities and wonders; World records; History; Miscellanea